The Influence of Flux Types and Cuts Dimension of Aluminum Recycling Cans - Kristoforus, Alexander; Anggono, Juliana; Risonarta, Victor Yuardi (Mechanova, 2017)
The consumption of drink cans worldwide reaches 6700 cans every second. Recycling of beverage cans is done to overcome the amount of garbage cans. There are two problems that arise in the process of recycling cans, namely the number of slag produced and the presence of a number of aluminum trapped in the slag. Both of these lead to low amount of product (yield recycling) and aluminum obtained (aluminum yield). In the previous study reported recycled yields for canned bodies of 59.5%, while for can cover 57.5%.In this study, the yield of recycled and aluminum yields were attempted to be increased by reducing the size of the can and using 2 drossing flux and 1 cover flux. In the cans body increased by 1.8-2.2% from 51,4% to 53,6%, while for cans lid increased by 1.1-2.2% from 66,4% to 68,6% by using different flux types. Reducing the cut dimension of the aluminium can, increase the yield of recycling by 2.9% from 51,4% to 54,3% for cans body and for canned lids increase by 4,3% from 66,4% to 70,7%.